Fever in childbirth: a mini-review of epidural-related maternal fever - Kinishi, Yuki; Koyama, Yoshihisa; Yuba, Tomoo; Fujino, Yuji; Shimada, Shoichi (Frontiers in Neuroscience, 2024)
Fever during childbirth, which is often observed in clinical settings, is characterized by a temperature of 38°C or higher, and can occur due to infectious and non-infectious causes. A significant proportion of non-infectious causes are associated with epidural-related maternal fever during vaginal delivery. Therapeutic interventions are required because fever has adverse effects on both mother and newborn. Effective treatment options for ERMF are lacking. As it is difficult to distinguish it from intrauterine infections such as chorioamnionitis, antibiotic administration remains the only viable option. We mentioned the importance of interleukin-1 receptor antagonist in the sterile inflammatory fever pathway and the hormonal influence on temperature regulation during childbirth, an important factor in elucidating the pathophysiology of ERMF. This review spotlighted the etiology and management of ERMF, underscoring recent advancements in our understanding of hypothalamic involvement in thermoregulation and its link to sterile inflammation. We propose to deepen the understanding of ERMF within the broader context of autonomic neuroscience, aiming to foster the development of targeted therapies.